If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3y + -18 = -13 Reorder the terms: -18 + -3y = -13 Solving -18 + -3y = -13 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + -3y = -13 + 18 Combine like terms: -18 + 18 = 0 0 + -3y = -13 + 18 -3y = -13 + 18 Combine like terms: -13 + 18 = 5 -3y = 5 Divide each side by '-3'. y = -1.666666667 Simplifying y = -1.666666667
| -4*1-12*1+7=0 | | 7n+14=22 | | -49+0x+16x^2=0 | | 21/2x+11/2x+1=12.50 | | 30*50x=x | | 7-X=38 | | (-9s^2+8s)+(5s^2-3s-2)= | | 5(3+5b)= | | Y-10=23 | | [h-240]=15 | | 8v-2=74 | | U=4(6n+32)+9(n+1) | | 4.8=1.8n-0.6n | | -3=x+-4 | | 36=1y-5y-12 | | 4.8=1.8-0.6 | | 20+10x+25x=5.50 | | 7(b-3)=7b+2 | | (-a^3-5a^2)+(4a^3+7a^2+9)= | | -10+-13x+3x^2=0 | | 7w-6=4(w+6) | | 0.6x+8=11 | | 5b+15=60 | | (5a^3-4a+2)+(-7a^3-5a+2)= | | m-15=25 | | 4x+1=2x+6 | | 10j=100 | | 4(m+5)+6=7(m+3)-8m | | 65=4b+5 | | 4x-6=10x+10 | | 4x-9=3-(x-2) | | 18k+27= |